Informing Parents about the Pharmacological and Invasive Behavior Management Techniques Used in Pediatric Dentistry - Mehrysa Paryab; Hossein Afshar; Razie Mohammadi (Tabriz University of Medical Sciences, 2014)
Background and aims. Parental acceptance and consent are important parameters in selecting the required behavior management technique during pediatric dental treatment. The present study sought to assess the effect of three different informing methods on the parental acceptance, consent and concern regarding the pharmacological and invasive behavior management techniques used in pediatric dentistry. Materials and methods. Ninety mothers of 3-6-year-old uncooperative children were selected and randomly assigned to three study groups. The parents in each group were initially asked to answer three questions related to their levels of 'acceptance', 'consent', and 'concern' toward the five behavior management techniques. Then, the information about the techniques was presented through a piece of writing in group I, verbal presentation in group II and showing a film in group III. At last, the parents answered the same three questions again. Score changes were analyzed by using ANOVA, correlations, Mann-Whitney U and Kruskal-Wallis methods. Results. There were no statistically significant differences in score changes of parental acceptance, consent and concern between the three groups, overall and in relation to each behaviour management technique (P > 0.05). Mothers with academic education revealed more statistically significant concern following presentation of information by film (P < 0.05). Conclusion. None of the presentation methods had a significant preference over the others; in selecting the behavioral management techniques, it is advisable to observe individual factors, such as the level of education of the mothers.